Maternal parenting stress in the face of early regulatory disorders in infancy: a machine learning approach to identify what matters most - Georg, Anna; Schröder-Pfeifer, Paul; Cierpka, Manfred; Taubner, Svenja (Frontiers in psychiatry, 2021)
Objective: Early regulatory disorders (ERD) in infancy are typically associated with high parenting stress (PS). Theoretical and empirical literature suggest a wide range of factors that may contribute to PS related to ERD. The aim of this study was to identify key predictors of maternal PS within a large predictor data set in a sample of N = 135 mothers of infants diagnosed with ERD. Methods: We used machine learning to identify relevant predictors. Maternal PS was assessed with the Parenting Stress Index. The multivariate dataset assessed cross-sectionally consisted of 464 self-reported and clinically rated variables covering mother-reported psychological distress, maternal self-efficacy, parental reflective functioning, socio-demographics, each parent’s history of illness, recent significant life events, former miscarriage/abortion, pregnancy, obstetric history, infants’ medical history, development, and social environment. Variables were drawn from behavioral diaries on regulatory symptoms and parental co-regulative behavior as well as a clinical interview which was utilized to diagnose ERD and to assess clinically rated regulatory symptoms, quality of parent-infant relationship, organic/biological and psychosocial risks, and social-emotional functioning. Results: The final prediction model identified 11 important variables summing up to the areas maternal self-efficacy, psychological distress (particularly depression and anger-hostility), infant regulatory symptoms (particularly duration of fussing/crying), and age-appropriate physical development. The RMSE (i.e., prediction accuracy) of the final model applied to the test set was 21.72 (R² = .58). Conclusions: This study suggests that among behavioral, environmental, developmental, parent-infant relationship, and mental health variables a mother’s higher self-efficacy, psychological distress symptoms particularly depression and anger-symptoms, symptoms in the child particularly fussing/crying symptoms, and age-inappropriate physical development are associated with higher maternal PS. With these factors identified, clinicians may more efficiently assess a mother’s PS related to ERD in a low-risk help-seeking sample.
Gesehen am 02.08.2021